Sensitivity analysis in MADM methods: Application of material selection - Yazdani, Morteza (2016)
Material selection is a core process in design and engineering, and its effective modeling remains a key strategic concern for production economics and management. The evaluation of materials is subject to various technical and subjective criteria, which may be conflicting in nature. Nonetheless, multi attribute decision making (MADM) models facilitate the complexity in realizing engineering objectives through some form of weight of attributes (criteria) assessment procedure. This study illustrates a new approach to gain those weights based on expert judgments and then select best material using ranking-based MADM methods. Specifically, we applied the SWARA method for the criteria weight assessment of the material selection process, and subsequently prioritize the candidate materials based on WASPAS and MOORA. Sensitivity analysis is performed to assess the robustness of the solution after a comparison is made between WASPAS and MOORA in ensuring the consistency of the results. We illustrate the problem on two real material selection case studies. © 2016, Kauno Technologijos Universitetas. All rights reserved.